Antimutagenic properties of fresh-water blue-green algae - Lahitová, N; Doupovcová, M; Zvonár, J; Chandoga, J; Hocman, G (Folia microbiologica, 1994)
The antimutagenic properties of whole fresh-water blue-green algae Aphanisomenon flos-aquae, marketed under the commercial name "Alpha Sun" were tested using the Ames test. Simultaneous addition of both algae and Nitrovin (a mutagen) to the test medium did not reduce the mutagenic activity. On the other hand, addition of freeze-dried blue-green algae to the test medium 2-24 h before the application of mutagen reduced its mutagenic activity.
Keywords: testy genotoxicity; Cyanobacteria; Fresh Water; Mutagenicity Tests; nitrovin; antimutagenní látky; Nitrovin; sladká voda; Salmonella typhimurium; sinice; Antimutagenic Agents